2014
DOI: 10.1007/s13277-014-2380-4
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 5 as potential molecular marker in cervical cancer and the KLF family profile expression

Abstract: Cervical cancer (CC) as other cancer types, presents molecular deregulations, such as the alterations of transcription factors. Krüppel-like factors (KLF) are a family of transcriptional regulators. They are involved in diverse cellular processes, such as proliferation, apoptosis, and angiogenesis among others. Here, we analyzed the expression of all 17 KLF members at messenger RNA (mRNA) level, and protein expression of the two most commonly altered KLF5 and KLF6 in cervical tissues. Fifty-nine cervical tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
1
31
2
Order By: Relevance
“…KLFs and SPs belong to the triple‐zinc finger family of transcription factors, a class of regulatory proteins with special secondary structures stabilized by a zinc ion . Activation of KLF/SP has been shown to contribute to tumorigenesis . We show that knocking down eEF2K reduces the protein levels of KLF5 and SP1 and hence leads to a reduction in the levels of bound KLF5/SP1 to the VEGF promoter, hence inhibiting the transcription of VEGF .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…KLFs and SPs belong to the triple‐zinc finger family of transcription factors, a class of regulatory proteins with special secondary structures stabilized by a zinc ion . Activation of KLF/SP has been shown to contribute to tumorigenesis . We show that knocking down eEF2K reduces the protein levels of KLF5 and SP1 and hence leads to a reduction in the levels of bound KLF5/SP1 to the VEGF promoter, hence inhibiting the transcription of VEGF .…”
Section: Discussionmentioning
confidence: 85%
“…33 Activation of KLF/SP has been shown to contribute to tumorigenesis. 34,35 We show that knocking down eEF2K reduces the protein levels of KLF5 and SP1 and hence leads to a reduction in the levels of bound KLF5/SP1 to the VEGF promoter, hence inhibiting the transcription of VEGF. KLF5 has been reported to aid the proliferation and migration of cancer stem cells in HCC.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Besides that, KLF5 expression can be regulated by miRNAs or posttranslation modification . In tumorigenesis, KLF5 has dual functions, being tumor suppressing gene and tumor promoting gene . Meanwhile, recent study revealed that KLF5 acetylation is crucial for the transition from tumor suppressor to tumor promoter .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, study of Eppk1 expression might shed lights on initiation and development of cervical cancer. In addition, Marrero-rodriguez et al found that KLF5 showed a gradual up-regulation trend in normal tissues, low-grade intraepithelial lesions, intraepithelial squamous lesions and CC samples, indicating that the up-regulation of KLF5 expression plays a certain role in the occurrence and development of cervical cancer [18]. We also demonstrated that the co-expression pattern between KLF5 and Eppk1 as well as Eppk1 is a target of KLF5 in CC cells, suggesting that inhibition of KLF5 expression by pharmacologic treatment (such as ML264) may be bene cial for treatment of CC.…”
Section: Discussionmentioning
confidence: 99%